“Family Trouble”: The 1975 Killing of Denise Hawkins and the Legacy of Deadly Force in the Rochester, NY Police Department - Ted Forsyth; Mallory Szymanski (Genealogy, 2024)
This paper examines the lineages of police violence, family trauma, and police reform through a case study of the Rochester police killing of Denise Hawkins in 1975. Michael Leach, a 22-year-old, white police officer, responded to a “family trouble” call involving a domestic dispute between Hawkins and her husband. When the 18-year-old, 100-pound Black woman emerged from the apartment, she held a kitchen knife. Within five seconds, Leach had shot and killed her, later claiming she endangered his life. Though Hawkins’ name is included in lists of Black women killed by police, little is known about her life and legacy. Using newspapers, police records, and oral history, we examine activists’ attempts to scale the call for justice for Denise Hawkins to the national level, the police department’s defense of Leach as the true victim in the incident, and the city leaders’ compromised efforts to establish a civilian oversight of police. Within the context of Rochester’s robust history of resistance to police violence, we argue that the reform efforts of the late 1970s ultimately failed to redress the police use of deadly force. Furthermore, when Michael Leach killed again in 2012—this time shooting his own son, whom he mistook for an intruder—his defense attorney successfully depicted Leach as the sympathetic figure. In shifting the focus to Denise Hawkins, this work contributes to the Black feminist call to memorialize Black women killed by police and suggests that the policies that protect the officers who use deadly force cause widespread, intergenerational harm to officers and their victims.